Peningkatan Produktifitas dan Variasi Usaha Ekonomi Perempuan Pengrajin Batik Desa Wonorejo Kecamatan Singosari Kabupaten Malang melalui Pelatihan Intensif Batik Tulis Kantil - Djoko Dwi Kusumojanto; Yana Respati Dewi; Adelia Shabrina Prameka; Andro Agil Nur Rakhmad (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Community service can be realized by implementing the empowerment of the surrounding community as a form of higher education's responsibility to Indonesia’s human development as a whole. So that development must be a social change that not only occurs at the level of life of the community but also in the role of the elements in it. The form of community service that will be carried out by the proposer team is through community empowerment with the target being Increasing Productivity and Economic Variation of Women Batik Artisans Wonorejo Village Singosari District of Malang through Intensive Training batik Tulis Kantil. The implementation of community service is carried out by providing vocational training in batik tulis, namely training in making batik tulis and crafting souvenirs from batik tulis made. Participants are brought in professional healers in order to learn and be built directly on how to correctly. In addition to making batik tulis, trainees are also given training in making souvenirs from batik cloth. The aim of this training is to form self-employed entrepreneurs and be part of improving Indonesia's creative economy..